Extending binary collocations - Gabrovšek, Dušan (ELOPE (Ljubljana), 2014)
The paper focuses primarily on the Sinclairian concept of extended units of meaning in general and on extended collocations in particular, investigating their nature and types. Such extended units are extremely varied and diverse; they are regarded as instances of the functioning of the coselection principle. Some extended forms are used far more commonly that the corresponding prototypical (binary) sequences. The final section delves into the ABCs of extended collocations in the context of lexicography, suggesting that dictionaries should make an effort to include a selection of such strings, especially for encoding tasks that are to be shown as examples of use. Most dictionaries incorporate very few such %loose% units, probably because of a powerful tradition to include as examples of use chiefly binary collocations and full sentences.
Keywords: razširjena pomenska enota; razširjene kolokacije; splošni dvojezični slovarji; splošni enojezični slovarji; vzorci